Noradrenaline has opposing effects on the hydraulic conductance of arterial intima and media. (21st March 2017) - Chooi, K.Y.; Comerford, A.; Sherwin, S.J.; Weinberg, P.D.
Abstract: The uptake of circulating macromolecules by the arterial intima is thought to be a key step in atherogenesis. Such transport is dominantly advective, so elucidating the mechanisms of water transport is important. The relation between vasoactive agents and water transport in the arterial wall is incompletely understood. Here we applied our recently-developed combination of computational and experimental methods to investigate the effects of noradrenaline (NA) on hydraulic conductance of the wall ( L p ), medial extracellular matrix volume fraction ( ϕ ECM ) and medial permeability ( K 1 1 ) in the rat abdominal aorta. Experimentally, we found that physiological NA concentrations were sufficient to induce SMC contraction and produced significant decreases in L p and increases in ϕ ECM . Simulation results based on 3D confocal images of the extracellular volume showed a corresponding increase in K 1 1, attributed to the opening of the ECM. Conversion of permeabilities to layer-specific resistances revealed that although the total wall resistance increased, medial resistance decreased, suggesting an increase in intimal resistance upon application of NA.